Harvard business review on talent management (Harvard Business School Pub., 2008)
If great talent is hard to find, it's even harder to keep. In today's competitive world, you need the best and the brightest on your team in order to stay ahead of the game. This book offers insights and strategies to make sure you recognize - and retain - your company's vital talent.